(untitled) (London Journal of Research In Management & Business, 2025)
This article discusses the techniques and means of forming the value-based orientations of a manager in the context of modern business realities. In particular, emphasis is placed on the transformation of a managers value chain at different stages of a companys development with the emergence of new technologies and the introduction of digitalization into business processes. Proprietary models of life cycles and assessments of the managers value-based orientations are developed, allowing to determine the conditions for successful adaptation of the company’s work to rapidly changing conditions and maintain competitiveness in the market thanks to the right management decisions.